(untitled) (International journal of artificial intelligence, 2024)
The game is an interesting tool for children to understand the world around them. Therefore, learning a foreign language through games is easy for students and prevents them from getting bored. The purpose of this article is to describe the games, to reveal its necessity and possibilities in teaching English. In addition, the correct distribution of time for the implementation of practical training through the game was considered